Modele niepełnosprawności jako determinanty przeobrażeń struktury podażowej rynku turystycznego dostępnego dla osób niepełnosprawnych - Zajadacz, Alina; Śniadek, Joanna (My University, 2014)
The research aims to answer a fundamental question: which of the disability models currently in use is optimal for creating “accessible tourism-oriented” amenities, as well as more detailed problems: (1) what is disability and what determines different disability models? (2) what types of tourism market supply available for the disabled do the different disability models suggest? (3) are the disability models complementary or mutually exclusive? (4) is the idea of social integration and inclusion of people with disabilities (PWD) while on tourist trips supported of the society? Data sources comprise selected literature and results of a survey conducted using the face-to-face method and the SurveyMonkey website from May 2013 to July 2014. The surveyed group included 619 people (82% were Polish, the other 18% were foreigners from: Russia, Germany, Portugal, Slovakia, Canada, Tunisia and the United Kingdom). The research showed that the different disability models – medical, social, geographical and economic – are useful when creating the tourism supply for the PWD. Using the research results, the authors suggested a model of “diversification of tourism market supply structure available for the disabled”, which includes different types of supply – from specialist to universal. This model has practical usage and can help entrepreneurs with the segmentation of tourism offers addressed to the PWD. The work is innovative, both in its theoretical approach (the review of disability models and their practical application in creating tourism supply) and empirical values – it provides current data for the social attitude towards the development of PWD tourism. Especially the presentation of a wide range of perception of disability as well as the simple classification of tourism supply that meets the varied needs of PWD, is a particular novelty of this chapter.
Keywords: medical model of disability; social model of disability; geographical model of disability; economic model of disability; accessible tourism